Effects of alcohol and task difficulty on visual tracking and inattentional blindness. - Bayless, Sarah J.; Harvey, Alistair J.; Keating, Stewart (Psychopharmacology, 2022)
Rationale: Inattentional blindness (IB) describes the failure to notice salient but unexpected stimuli in one's focal visual field. It typically occurs while performing a demanding task (e.g. tracking and counting basketball passes), which consumes attentional resources. Alcohol intoxication is also known to reduce attentional resources, thereby potentially increasing IB and disrupting task performance. Objectives: To test the extent to which acute alcohol and task difficulty disrupt counting performance and increase the rate of IB across two experimental tasks. Methods: To test the effects of alcohol consumption and task difficulty on IB, we used the Simons and Chabris (Percept 28:1059-1074, 1999) and Simons (2010) "gorilla in our midst" basketball clip in experiment 1 and abstract but analogous stimuli presented in a computerised alternative to that task in experiment 2. Results: IB was associated with increased (counting) task difficulty but not alcohol consumption. However, counting accuracy was impaired by both alcohol and increased task difficulty, with the largest detriment being for alcohol participants who noticed the salient but unexpected stimulus. Conclusion: The absence of alcohol effects on IB in both experiments was unexpected and warrants further investigation in a field vs lab study comparison and in combination with baseline cognitive measures to test for alcohol expectancy and task compensation effects.